2020
DOI: 10.5194/wes-2020-3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controls-Oriented Model for Secondary Effects of Wake Steering

Abstract: Abstract. This paper presents a model to incorporate the secondary effects of wake steering in large arrays of turbines. Previous models have focused on the aerodynamic interaction of wake steering between two turbines. The model proposed in this paper builds on these models to include yaw-induced wake recovery and secondary steering seen in large arrays of turbines when wake steering is performed. Turbines operating in yaw misaligned conditions generate counter-rotating vortices that entrain momentum and cont… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 25 publications
(41 reference statements)
1
40
0
Order By: Relevance
“…Additionally, more realistic wake models are being developed based on new insights into the physics of wake steering that may impact how susceptible wake steering is to wind direction variability. For example, the curled wake model presented by Martínez-Tossas et al (2019) and the Gauss-curl hybrid wake model developed by King et al (2020), inspired by observations from CFD simulations discussed by Fleming et al (2018), consider how trailing vortices resulting from yaw misalignment interact with the wake to not only deflect it but also change its shape. Fleming et al (2018) discuss how the trailing vortices created by multiple turbines can merge, creating large-scale structures in the flow that could potentially be used to entrain higher energy flow from above the wind farm.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, more realistic wake models are being developed based on new insights into the physics of wake steering that may impact how susceptible wake steering is to wind direction variability. For example, the curled wake model presented by Martínez-Tossas et al (2019) and the Gauss-curl hybrid wake model developed by King et al (2020), inspired by observations from CFD simulations discussed by Fleming et al (2018), consider how trailing vortices resulting from yaw misalignment interact with the wake to not only deflect it but also change its shape. Fleming et al (2018) discuss how the trailing vortices created by multiple turbines can merge, creating large-scale structures in the flow that could potentially be used to entrain higher energy flow from above the wind farm.…”
Section: Discussionmentioning
confidence: 99%
“…In Bastankhah and Porté-Agel (2019), a detailed wind-tunnel-based study showed that for arrays of turbines performing wake steering, the best strategy is for each successive turbine in a column to have a reduced yaw offset from the one directly upstream. Recently, the Gauss-curl hybrid (GCH) model was introduced in King et al (2019). This model proposes an analytic implementation of the vortices of the curl model of Martínez-Tossas et al (2019) to modify an underlying Gauss model of Bastankhah and Porté-Agel (2014); Niayifar and Porté-Agel (2015); Bastankhah and Porté-Agel (2016).…”
Section: Engineering Modelsmentioning
confidence: 99%
“…This model proposes an analytic implementation of the vortices of the curl model of Martínez-Tossas et al (2019) to modify an underlying Gauss model of Bastankhah and Porté-Agel (2014); Niayifar and Porté-Agel (2015); Bastankhah and Porté-Agel (2016). This latest model will be used in this study and a brief overview of its theory will be included in this paper; see King et al (2019) for a full description.…”
Section: Engineering Modelsmentioning
confidence: 99%
See 2 more Smart Citations